ABCG36/PEN3/PDR8 Is an Exporter of the Auxin Precursor, Indole-3-Butyric Acid, and Involved in Auxin-Controlled Development - Aryal, Bibek; Huynh, John; Schneuwly, Jerôme; Siffert, Alexandra; Liu, Jie; Alejandro, Santiago; Ludwig-Müller, Jutta; Martinoia, Enrico; Geisler, Markus (Frontiers in Plant Science, 2019)
The PDR-type ABCG transporter, ABCG36/PDR8/PEN3, is thought to be implicated in the export of a few structurally unrelated substrates, including the putative auxin precursor, indole-3-butyric acid (IBA), although a clear-cut proof of transport is lacking. An outward facing, lateral root location for ABCG36 fuelled speculations that it might secrete IBA into the rhizosphere. Here we provide strong evidence that ABCG36 catalyses the export of IBA - but not of indole-3-acetic acid - through the plasma membrane. ABCG36 seems to function redundantly with the closely related isoform ABCG37/PDR9/PIS1 in a negative control of rootward IBA transport in roots, which might be dampened by concerted, lateral IBA export. Analyses of single and double mutant phenotypes suggest that both ABCG36 and ABCG37 function cooperatively in auxin-controlled plant development. Both seem to possess a dual function in the control of auxin homeostasis in the root tip and long- range transport in the mature root correlating with non-polar and polar expression profiles in the lateral root cap and epidermis, respectively.